1977
DOI: 10.1073/pnas.74.8.3268
|View full text |Cite
|
Sign up to set email alerts
|

Identification of synaptic acetylcholine receptor sites in retina with peroxidase-labeled α-bungarotoxin

Abstract: An a-bungarotoxin-horseradish peroxidase colijugate, which binds specifically to nicotinic acetylcholine receptors, was synthesized. This conju ate was bound by 5-7% of the synapses in the inner plexiform layer of the chicken retina. Bipolar ribbon synapses as well as amacrine synapses bound the conjugate. The idea that certain neurotransmitter receptors are located predominantly at chemical synapses has been supported by acetylcholine (AcCh) sensitivity mapping of the skeletal muscle membrane (1) and parasymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…(Baughman & Bader, 1977). This is consistent with other evidence which suggests that cholinergic synapses in the retina occur predominantly in the inner plexiform layer and that a sub-population of amacrine cells is cholinergic (Nichols & Koelle, 1968;Neal, 1976a;Ross & McDougal, 1976;Masland & Ames, 1976;Vogel, Maloney, Ling & Daniels, 1977;Massey & Neal, 1978). If the sites of [3H]-choline uptake in the rat retina are similar to those in the chicken (but see Neal (1976b) for the importance of species differences in the retina) then the [3H]-ACh released by potassium depolarization presumably originated from amacrine and/or bipolar cells.…”
Section: Discussionsupporting
confidence: 81%
“…(Baughman & Bader, 1977). This is consistent with other evidence which suggests that cholinergic synapses in the retina occur predominantly in the inner plexiform layer and that a sub-population of amacrine cells is cholinergic (Nichols & Koelle, 1968;Neal, 1976a;Ross & McDougal, 1976;Masland & Ames, 1976;Vogel, Maloney, Ling & Daniels, 1977;Massey & Neal, 1978). If the sites of [3H]-choline uptake in the rat retina are similar to those in the chicken (but see Neal (1976b) for the importance of species differences in the retina) then the [3H]-ACh released by potassium depolarization presumably originated from amacrine and/or bipolar cells.…”
Section: Discussionsupporting
confidence: 81%
“…Specifically, observations in chick (Vogel et al 1977), mouse (Pourcho 1979), goldfish (Zucker and Yazulla 1982), and turtle (James and Klein 1985) all demonstrated aBgt binding associated with bipolar cells or amacrine-bipolar synapses. In addition, previous work from this laboratory (Keyser et al 1993) showed aBgt-sensitive nAChR (a8 subunits) antibody labeling of bipolar cells in the avian retina.…”
Section: Putative Role Of A7 Nachrs In Visual Processingmentioning
confidence: 99%
“…All synapses between retina neurons and muscle cells are terminated in 3-10 days depending on the developmental age of the neurons. The half-lives of synapses between muscle cells and retina neurons from 8-, 12-, or (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…All synapses between retina neurons and muscle cells are terminated in 3-10 days depending on the developmental age of the neurons. The half-lives of synapses between muscle cells and retina neurons from 8-, 12-, or (3)(4)(5)(6)(7)(8).In this report we examine the specificity of synapse formation by retina neurons. The neurons were cultured with striated muscle cells which also possess abundant nicotinic ACh receptors, to determine whether retina neurons form synapses with muscle cells and whether muscle cells and retina neurons displace one another or are competitive targets for synapse formation by retina neurons that synthesize ACh.…”
mentioning
confidence: 99%